Oral exposure to polyethylene microplastics induces inflammatory and metabolic changes and promotes fibrosis in mouse liver. - Madjid Djouina; Christophe Waxin; Laurent Dubuquoy; David Launay; Cécile Vignal; Mathilde Body-Malapel (Ecotoxicology and Environmental Safety, 2023)
Accumulating evidence shows widespread contamination of water sources and food with microplastics. Although the liver is one of the main sites of bioaccumulation within the human body, it is still unclear whether microplastics produce damaging effects. In particular, the hepatic consequences of ingesting polyethylene (PE) microplastics in mammals are unknown. In this study, female mice were fed with food contaminated with 36 and 116 µm diameter PE microbeads at a dosage of 100 µg/g of food for 6 and 9 weeks. Mice were exposed to each type of microbead, or co-exposed to the 2 types of microbeads. Mouse liver showed altered levels of genes involved in uptake, synthesis, and β-oxidation of fatty acids. Ingestion of PE microbeads disturbed the detoxification response, promoted oxidative imbalance, increased inflammatory foci and cytokine expression, and enhanced proliferation in liver. Since relative expression of the hepatic stellate cell marker Pdgfa and collagen deposition were increased following PE exposure, we assessed the effect of PE ingestion in a mouse model of CCl4-induced fibrosis and showed that PE dietary exposure exacerbated liver fibrogenesis. These findings provide the first demonstration of the adverse hepatic effects of PE ingestion in mammals and highlight the need for further health risk assessment in humans.